Sensing the electrical properties of roots: A review - Ehosioke, S. (2021)
We review the potential and limitations of low‐frequency electrical techniques for root zone investigation, discuss the mechanisms behind electrical conduction and polarization in the soil–root continuum, and address knowledge gaps. A range of electrical methods for root investigation is available. Reported methods using current injection in the plant stem to assess the extension of the root system lack robustness. Multi‐electrode measurements are increasingly used to quantify root zone processes through soil moisture changes. They often neglect the influence of root biomass on the electrical signal, probably because it is yet to be well understood. Recent research highlights the potential of frequency‐dependent impedance measurements. These methods target both surface and volumetric properties by activating and quantifying polarization mechanisms occurring at the root segment and cell scale at specific frequencies. The spectroscopic approach opens up a range of applications. Nevertheless, understanding electrical signatures at the field scale requires significant understanding of small‐scale polarization and conduction mechanisms. Improved mechanistic soil–root electrical models, validated with small‐scale electrical measurements on root systems, are necessary to make further progress in ramping up the precision and accuracy of multi‐electrode tomographic techniques for root zone investigation.